2019
DOI: 10.22201/ib.20078706e.2019.90.2528
|View full text |Cite
|
Sign up to set email alerts
|

An updated checklist of the Mexican species of Dalbergia (Leguminosae) to aid in its conservation efforts

Abstract: An updated checklist of the Mexican species of Dalbergia (Leguminosae) to aid in its conservation effortsUn listado actualizado de las especies mexicanas de Dalbergia (Leguminosae) para ayudar en los esfuerzos para su conservación

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Phylogenetic analysis of the nuclear internal transcribed spacer (ITS) supports the monophyly of the genus (Vatanparast et al 2013), which has been confirmed in several studies of chloroplast variation (Hartvig et al 2015;Hassold et al 2016;Li et al 2017). Numerous arborescent species are known to form durable and beautifully colored heartwood (Prain 1904;De Carvalho 1997;Bosser and Rabevohitra 2002;Cervantes et al 2019). Several species are highly sought-after, especially for the production of high-quality furniture and musical instruments (Barrett et al 2010), and some species are used in traditional medicine (Liu et al 2017).…”
mentioning
confidence: 78%
“…Phylogenetic analysis of the nuclear internal transcribed spacer (ITS) supports the monophyly of the genus (Vatanparast et al 2013), which has been confirmed in several studies of chloroplast variation (Hartvig et al 2015;Hassold et al 2016;Li et al 2017). Numerous arborescent species are known to form durable and beautifully colored heartwood (Prain 1904;De Carvalho 1997;Bosser and Rabevohitra 2002;Cervantes et al 2019). Several species are highly sought-after, especially for the production of high-quality furniture and musical instruments (Barrett et al 2010), and some species are used in traditional medicine (Liu et al 2017).…”
mentioning
confidence: 78%
“…Although these species are established in different clusters, all have in common provide Materials, and valuable high-quality wood that are gathered from woodlands. A recent indiscriminate exploitation of the fine wood provided by Dalbergia species has brought a national effort for their conservation [54]. Several wild species of Phaseolus have recently being included in the IUCN Red List of threatened species [55].…”
Section: Threatened or Endangered Speciesmentioning
confidence: 99%
“…We identify muk as the shrub/ small tree Dalbergia glabra, 'muk enchantment' (Roys, 1931: 266), which has white flowers. It has both practical and medicinal uses and is particularly abundant in Campeche (GBIF Backbone Taxonomy, 2017; Cervantes, Linares and Quintero, 2019). This identification conforms to a common Classic Maya practice of deriving toponyms from features of the local geography.…”
Section: The Toponymic Title Of El Palmar Campechementioning
confidence: 73%